Körperkoordinations test für Kinder: A short form is not fully satisfactory - Biino, Valentina; Giustino, Valerio; Guidetti, Laura; Lanza, Massimo; Gallotta, Maria Chiara; Baldari, Carlo; Battaglia, Giuseppe; Palma, Antonio; Bellafiore, Marianna; Giuriato, Matteo; Schena, Federico (Frontiers in Education, 2022)
Assessment of Motor Competence (MC) is crucial to find deficiencies in children’s motor development. Due to the need to ensure validity, reliability and feasibility, the selection in contemporary testing batteries is a difficult task. Many papers report the validity of KTK test in describing MC in school ages. KTK consists of 4 four separate items: walking back, jumping sideway, moving sideways, and hopping for height. some authors suggested the use of a short version of KTK that includes 3 items excluding one subtest: hopping for height. The aim of this study was to evaluate the effectiveness of short versions of Körperkoordinationstest für Kinder (KTK). A sample of 2231 participants (boys: n=1188; girls: n=1043; age range: 6-12 years) were recruited from Italian schools, from January 2019 to February 2020 and they performed the complete version of KTK. Stepwise linear regression was performed on the dataset to evaluate the ideal number of variables to describe the KTK test, short-form version. Data for both sexes and all ages indicated that, considering the item combinations of each short version, the highest R squares were obtained in those that included exactly the deleted subtest (ranging from 0.881 to 0.979). The adoption of a short form does not seem to provide a fully satisfactory condition for measuring MC in children 6-12 years.